Firm Structural Traits and Stock Performance of Consumer Goods Sector Listed in the Nigerian Exchange Group During and Post Covid-19 Pandemic - Samuel Ejiro Togbolo-Uwhejevwe; Fortune Ogheneworo Erume; Nkechi Emeka-Nwokeji; Joshua Kenechukwu Onuora (JOURNAL OF MANAGEMENT, ACCOUNTING, GENERAL FINANCE AND INTERNATIONAL ECONOMIC ISSUES, 2025)
This study objective is to close the gap on the relationship between firm traits and stock performance in Nigeria during a time of unparalleled global upheaval. By employing quantitative analysis to empirically demonstrate the study result. Stock performance (SP) is the most active financial indicator in any firm. Thus, SP responded to the historic slowdown in economic activity brought on by COVID-19. The study used longitudinal and ex post facto research design. The population for the study consists of 20 quoted firms on the Nigerian Exchange Group. The sampled consist of 17 firms with available and accessible annual reports that covered the study period of 2020, 2021, 2022 and 2023 was used, thus the study acknowledged 2020-2021 as COVID year, while 2022-2023 as post COVID year. The findings indicated MAC had a significant favorable impact on SP across both time periods, ROA significantly improved SP throughout the COVID-19 period, while FLEV had a negative impact on SP during the COVID-19 era. The study concluded that, MAC took center stage, suggesting that investor confidence in bigger, better-capitalized firms became more significant. As the market place more emphasis on stability and high valuations than on operational effectiveness or taking risks, ROA, BUR, ASS, and FAGE lost significance. It was recommended that Although Firm Size (FSIZE) was negatively impacted during the COVID-19 pandemic, this does not imply that businesses should drastically reduce their workforce.